Colon in Loop Examination Technique in CA Recti Cases at Radiology Installation RSPAU Dr. Suhardi Hardjolukito Yogyakarta - Rizka R. Gafur; Anisa Nur Istiqomah; Widya Mufida (Jurnal Kesehatan Metro Sai Wawai, 2025)
Background: The colon in loop (CIL) examination at the Radiology Department of RSPAU Dr. Suhardi Hardjolukito employs the following projections: single-contrast AP, lateral, RPO, and LPO, followed by double-contrast AP, RPO, LPO, and post-evacuation AP. The procedure utilizes water-soluble contrast media without the use of a balloon to secure the catheter. Methods: This study adopts a qualitative approach using a case study method. Subjects include one radiology specialist and three radiographers. The research was conducted from August 2024 to September 2025. Data were collected through direct observation, interviews, and documentation, followed by data processing, analysis, and conclusion drawing. Results: Findings from the Radiology Department of RSPAU Dr. Suhardi Hardjolukito indicate that the use of water-soluble contrast media is safer for patients at risk of perforation, as it is easily absorbed by the body and carries a low risk of complications. Additionally, the use of a catheter without a balloon proves effective, as it does not interfere with rectal visualization and reduces the risk of irritation or excessive pressure in the area. Conclusion: The CIL examination using water-soluble contrast media and a catheter without a balloon is a safe and effective method, especially for patients suspected of having a risk of perforation. The choice of contrast media should be tailored to the patient's clinical condition, and the use of fluoroscopy is recommended to enhance efficiency and accuracy in the examination procedure.